Familiarity and Attitude toward Pharmacovigilance among Pharmacy Academics in Jordanian Universities: A Cross-Sectional Study - Taybeh, Esra’; Al-Alami, Zina; Alsous, Mervat; Abdelwahab, Ghada (Jordan Journal of Pharmaceutical Sciences, 2020)
Background: Awareness of pharmacovigilance among pharmacy academics increases the students and graduated pharmacists’ knowledge and skills in reporting adverse drug reactions (ADRs). Purpose: The aims of this study are to assess the level of awareness about pharmacovigilance among pharmacy school academics in Jordan and to explore the current pharmacovigilance education, from the academics’ point of view. Method: A paper-based 24-item questionnaire was distributed in eight schools of pharmacy that accepted to participate. Results: The questionnaire was completed by 87 pharmacy academics. Most participants were familiar with the concept of pharmacovigilance (79.3%) and the majority (96.5%) agreed to implement ADR reporting in the school curriculum. Despite this positive attitude, only 26.4% of participants had previously attended a workshop about pharmacovigilance and 36.8% were able to educate the students on how to report ADRs. Conclusion: Pharmacy school academics in Jordan have a good familiarity and positive attitude about pharmacovigilance. However, the inclusion of topics about detecting, preventing, and reporting ADRs to the current school curricula is recommended.